3D face modeling, analysis and recognition - Daoudi, Mohamed, Ph. D.; Srivastava, Anuj; Veltkamp, Remco C., 1963- (Wiley-Blackwell, 2013)
Presents methodologies for modeling, analysis and recognition of shapes of facial surfaces, from fundamental ideas in geometry and shape analysis, to cutting-edge applications This text presents methodologies for analyzing shapes of facial surfaces, develops computational tools for analyzing 3D face data, and illustrates them using state-of-the-art applications. The methodologies chosen are based on efficient representations, metrics, comparisons, and classifications of features that are especially relevant in the context of 3D measurements of human faces. These frameworks hav.